Between Sect and Secularism: The Mediated Ambiguities of the Syrian Nation State (Global Media Journal - German Edition, 2021)
This paper examines narrative discourses of the Syrian loyalist TV channel Sama TV in the light of Syria’s current armed conflict, demography, and regional geopolitics. The focus is on the tense relationship between secularism and religious representations on the channel. Compared to state television, private channel Sama TV has more room for maneuver to embrace a new form of religious presence that challenges the ideological secularism of the Syrian nation state. The national “mythscapes” of Syria, simultaneously a secular and (Sunni) Muslim nation, characterized by acertain ambiguity, are consequently reinforced.
Keywords: collective identity; cult; martyrs; mediated “mythscapes”; mobilization media; narrative discourses; national symbols; Sama TV; secularism; Syrian television